Debt and Repayment System for Chili Traders based on an Islamic Economic Perspective in Kerongkong Village, Lombok Timur - Washimatul Bestari; Busaini, Busaini; Aminu Umaru (Tinta Emas Publisher, 2024)
This study aims to determine the Debt and Return System carried out by Chilli Traders according to Islamic Economics in Kerongkong Village, Suralaga District, East Lombok Regency. This research uses a qualitative approach with a case study method. Data collection techniques in this study used observation techniques, in-depth interviews, and documentation. Data collection and determination of each informant was carried out using purposive and snowball techniques. The data sources used in this research are primary and secondary data. Data checking or validation uses triangulation techniques, namely source triangulation and method triangulation. The results of this study indicate that the debt and return system carried out by chilli traders in Kerongkong Village, Suralaga Subdistrict, East Lombok Regency according to Islamic economics is not optimal, this is evidenced by the violation of some adab in debt and Islamic economic principles in the implementation of the debt system carried out. This research also shows that chilli traders in Kerongkong Village still do not know and understand the procedures for debt that are justified and prohibited in Islam.